2011
DOI: 10.1039/c0jm03880f
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of transition metal substitution in conversion electrodes for lithium-ion batteries

Abstract: Different solid solutions in the Fe x Co 1Àx C 2 O 4 $2H 2 O system have been prepared in the form of nanoribbons by a reverse micelles method. The orthorhombic crystallographic structure differs from the monoclinic massive products FeC 2 O 4 $2H 2 O and CoC 2 O 4 $2H 2 O. The dehydration process is studied by thermal analysis to prepare the anhydrous solid solution oxysalts, in which the nanoribbonshaped particles are preserved and a porous system is developed. Anhydrous mixed oxalates are used for the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 12 publications
2
54
0
Order By: Relevance
“…This reaction is similar to conversion reactions, but the reaction products are metal and lithium oxalate instead of Li 2 O, which is more noticeable in the case of conversion reactions for metal oxides. 45 Using X-ray absorption and Fourier transform infrared studies, Aragon et al 25 also observed this similarity in the formation of Li 2 C 2 O 4 when lithiated (reduced). Upon charging (oxidation), the relative intensity of the XRD pattern gradually increased and was completely recovered to its state before discharge (Figure 3a).…”
Section: Nickel Oxalate Dihydrate Nanorods In Libs H-j Oh Et Almentioning
confidence: 91%
See 4 more Smart Citations
“…This reaction is similar to conversion reactions, but the reaction products are metal and lithium oxalate instead of Li 2 O, which is more noticeable in the case of conversion reactions for metal oxides. 45 Using X-ray absorption and Fourier transform infrared studies, Aragon et al 25 also observed this similarity in the formation of Li 2 C 2 O 4 when lithiated (reduced). Upon charging (oxidation), the relative intensity of the XRD pattern gradually increased and was completely recovered to its state before discharge (Figure 3a).…”
Section: Nickel Oxalate Dihydrate Nanorods In Libs H-j Oh Et Almentioning
confidence: 91%
“…24 Tirado's group also suggested a possible mechanism during the first lithiation: MC 2 O 4 +2Li + +2e − → M+Li 2 C 2 O 4 . [25][26][27] By contrast, it is not clear whether the presence of oxalate ions can be solely ascribed to the formation of Li 2 C 2 O 4 because the oxalate ions were present in both unreacted MC 2 O 4 (M: Co) and Li 2 C 2 O 4 . 25 Interestingly, thermal decomposition of metal oxalates as precursors usually leads to the production of metal oxides.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations